Intermediate analysis of a phase II trial assessing gemcitabine and cisplatin in locoregional or metastatic penile squamous cell carcinoma. (27th April 2015) - Houédé, Nadine; Dupuy, Laura; Fléchon, Aude; Beuzeboc, Philippe; Gravis, Gwenaëlle; Laguerre, Brigitte; Théodore, Christine; Culine, Stéphane; Filleron, Thomas; Chevreau, Christine
Abstract : Objective: To perform a phase II study evaluating a combination of gemcitabine and cisplatin in a population of patients with squamous cell carcinoma (SCC) of the penis and unresected locoregional lymph nodes and/or distant metastases, who had a poor prognosis with no standard of chemotherapy. Patients and Methods: Eligible patients had histologically confirmed SCC of the penis with unresected locoregional lymph nodes and/or distant metastases, at initial diagnosis or at relapse, and measurable disease as defined by Response Evaluation Criteria in Solid Tumors (RECIST) criteria. Patients were treated with a combination of gemcitabine 1250 mg/m 2 on day 1 over 30 min and cisplatin 50 mg/m 2 on day 1 over 1 h, every 2 weeks. The primary endpoint was the objective response rate; secondary endpoints were time to progression (TTP) and overall survival (OS). Results: In all, 25 patients were included in the first phase of the study between February 2004 and January 2010 and received a median of five cycles. For the intent‐to‐treat population, two patients (95% confidence interval [CI] 0.98–26.0) presented an objective response and 13 patients (52%) had stable disease (95% CI 35.5–76.8). The median TTP was at 5.48 months (95% CI 2.40–11.73). After a median follow‐up of 26.97 months (95% CI 17.77, not reached), nine patients were still alive. The median OS and 2‐year OS rate were respectively estimated at 14.98 months (95% CI 9.76–32.9) and 39.32% (95% CI 19.15–59.03). Eleven patients had a serious adverse event (44%), 24% being relied to chemotherapy. Conclusion: Every 2 weeks' administration of the combination of gemcitabine and cisplatin showed non‐significant responses in patients with unresected locoregional or metastatic penile SCC. Despite manageable side‐effects, this combination cannot be recommended as a standard of care, due to disappointing response rates seen in this negative study. Further regimens should be explored to improve the OS of these patients with poor prognosis.